PENERAPAN AKUNTANSI DAN KESESUAIANYA DENGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM): Studi kasus Pada UMKM Kabupaten Kerinci - Zachari Abdallah; Maryanto Maryanto (Bussman Journal : Indonesian Journal of Business and Management, 2022)
According to (Bank Indonesia, 2015) Business feasibility, financial aspects, marketing aspects and aspects of human resources (labor) are MSME problems that have been felt so far by the Bank. The lack of a common mindset between bank requirements that must be met by MSMEs, including the availability of financial statements and bussines plans (business development plans) is an obstacle that causes the lack of access to MSME finances. According to (Rudiantoro & Siregar, 2012) The great potential of Enterprises, Micro, Small, and Medium Enterprises (MSMEs) is often constrained by capital problems to develop businesses. If MSMEs do not innovate and develop their business, then there could be many MSME actors who cannot continue their business. For a company that will win the competition in the market segment, then it must reach the point of quality in all aspects. Of course, not only paying attention to quality products, but those that are cheaper and have better service will be the target of consumers. Most MSMEs only use personal funds (capital) in running their business and there is no separation between personal money and company money, even though to develop a business for the better requires considerable funds and separation between personal money and company money. The objectives of this study are: 1.To determine the application of SAK ETAP in the presentation of financial statements to MSMEs in Kerinci Regency.2.         To find out the obstacles faced in the application of SAK ETAP to MSMEs in Kerinci Regency. This research uses a qualitative approach. (Moeloeng 2012:6) states that qualitative research is research that intends to understand the phenomenon of what the subject of the study experiences for example behavior, perception, motivation, action, etc., holistically, and by means of descriptions in the form of words and language, in a special context that is natural and by utilizing various scientific methods. Sugiyono (2010: 14) states that qualitative methods are used to obtain in-depth data, namely data that contains meaning. The outputs of this study are: 1. Publication in Scientific Journals The results of this research are expected to be published in accredited national journals that support the profession. 2. Intellectual Property Rights (Intellectual Property Rights) The results of this research are important to confirm the findings of lecturers as one of the protections of Intellectual Property Rights resulting from inventions in the general public.